Ill-Treatment Formulas Sensu Largo and the Jurisprudence of the ECtHR with Special Regard to Central Europe - Janusz-Pohl , Barbara (The ECHR at 70: The Central European Narrative, 2025)
This study is not intended to be purely descriptive; rather, it delves into the intricate standards established by the European Court of Human Rights (ECtHR) regarding the prohibition of torture and other forms of ill-treatment. These standards are well articulated and form a crucial foundation for human rights protection in Europe. In this paper, we will focus specifically on the prohibition of torture and related forms of ill-treatment as interpreted and applied in the case law of the ECtHR. Our analysis will encompass definitional challenges and will trace the significant legal advancements that have emerged from this case law, allowing us to identify areas of concern where Article 3 is being violated across various countries, along with the corresponding legal repercussions. We will begin by examining general statistics that illustrate the prevalence of Article 3 violations, followed by a detailed analysis of individual cases from Poland and Hungary that exemplify these violations. The discussion will culminate in an examination of two significant judgments related to Article 3 that address the handling of evidence in criminal proceedings. In these cases, the Court emphasises the necessity of excluding unlawfully obtained evidence, drawing on Article 3 in conjunction with Article 6 of the Convention. It is noteworthy that the standards for excluding evidence in criminal proceedings exhibit considerable variation across national legal systems and, in many instances, are not explicitly regulated. As such, the Court's guidelines serve as a vital reference point for both legal practitioners and policymakers. Finally, the discussion will conclude with insights that highlight the evolving trends in the case law of the ECtHR, particularly concerning Central and Eastern European countries. The interpretations and findings presented in this study carry significant implications for the ongoing struggle against torture and ill-treatment in the region. Keywords: Prohibition of torture, ill-treatment, Article 3 ECHR, admissibility of evidence, violation of the ECHR